Parents` perceived service quality, satisfaction and trust of a childcare center : implication on loyalty - Omar, Nor Asiah; Nazri, Muhamad Azrin; Abu, Nor Khalidah; Omar, Zoharah (World Business Institute, 2009)
The aim of this study is to investigate the impact of parent’s perceived service quality on satisfaction and trust. It also explores the relationship between satisfaction, trust and loyalty in a childcare centre. Perceived service quality in a childcare centre has received increasing attention by researchers during the past decade. Research evidence has revealed that perceived service quality has an influence on satisfaction and trust. The data for this research were collected from 201 respondents in Kuala Lumpur and Selangor via survey technique. A comprehensive conceptual model was developed and tested by structural equation modeling using AMOS program. The findings unveil that perceived service quality is positively related to parent satisfaction and trust. In turn, parent’s satisfaction is the most influential determinant of trust. Furthermore this paper delineates several interesting findings that, trust holds a pre-eminent role in the formation of parent’s loyalty towards the childcare centre. However, parent’s satisfaction has no direct impact on loyalty. Implications of the findings, potential limitations of the study and directions for future research are suggested.